Tuvalu : 2018 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
Tuvalu is a fragile micro state. The country's remoteness, narrow production base, and weak banking sector constrain private sector activity, leaving public expenditure as the main source of growth. The DSA finds that Tuvalu remains at high risk of debt distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet